VOC concentrations in houses in Japan: correlations with housing characteristics and types of ventilation - Sangin Park; Naoki Kagi; Wataru Umishio; Kenichi Hasegawa; Teruaki Mitamura; Jo Tamura (Journal of Asian Architecture and Building Engineering)
Volatile organic compounds (VOCs) can cause health problems for residents and are one of the causes of sick building syndrome. Therefore, this study measured VOCs in 116 houses in the winter and 66 in the summer in Japan, including detached and apartment houses. The diffusion sampler method was used for field measurements. Living rooms and bedrooms were sampled to confirm the concentration characteristics and differences between the two locations. In addition, a questionnaire survey was conducted to identify the type of house, residence period, and type of ventilation system used. Most VOC concentrations did not exceed the Japanese guidelines during the winter and summer. However, in the winter, the acetaldehyde concentrations exceeded the Ministry of Health, Labour, and Welfare of Japan (MHLW) guidelines, reaching 14.7% in the living room and 12.9% in the bedroom. The VOC concentration was higher in apartments than in detached houses. Even among detached houses, built-for-sale houses had slightly higher VOC concentrations than custom-made houses. The concentration of VOCs according to characteristics, such as the residence period, did not show significant differences except for acetaldehyde. In houses with unbalanced ventilation, formaldehyde and other VOC concentrations were higher in the living room and bedroom than in houses with balanced ventilation.